Optical coherent tomography in the diagnosis of inflammatory and ischemic optical neuropathies (clinical cases) - Moyseyenko, Nataliya (ScienceRise: Medical Science, 2021)
Optic neuropathy is a group of diseases of the optic nerve. Using diagnostic techniques such as ophthalmoscopy and perimetry diagnosis are insufficient, as the found abnormalities are not specific for either inflammation or ischemia. Establishing the predominant factor in the pathogenesis of neuropathy is crucial in determining the method of treatment. The aim of the study: to investigate the features of optic nerve damage using optical coherent tomography (OCT) in optic neuropathy in the acute period. Materials and methods: two patients with visual impairment were examined. Result. Patient G. had concomitant rheumatoid arthritis with unregulated Methotrexate therapy. OCT revealed edema of the nerve fibre layer convinced of the predominance of inflammatory neuropathy (atypical neuritis). Pulse therapy with corticosteroids was prescribed, which gave a positive functional effect. A patient O. with pneumonia on the background of Covid-19 with a history of OST showed a decrease in the thickness of the layer of nerve fibres in the lower segment, and in the angio mode – drusen of the optic disc. Conclusions. Thus, the use of OCT for the diagnosis of optic neuropathies in the acute period showed that under conditions of inflammatory lesions is more characteristic of edema and an increase in the thickness of the layer of nerve fibres. In ischemic neuropathy, on the contrary, a decrease in the thickness of nerve fibres is more characteristic, which correlates in location with the localization of scotoma in the field of view. Therefore, the use of OCT of the optic nerve will help in understanding the pathogenesis of forms of optic neuropathy. This will help in the choice of treatment tactics